Analyze the Characteristics of Susceptible Groups to Reduce the Pressure of Epidemic Prevention and Control - Tian, Yuan; Yang, Jiawei; Cai, Tianlong; Zhang, Yi; lv, Ge (International Journal of Computer Science and Information Technology, 2024)
This paper seeks to investigate the traits of those who are susceptible to epidemic transmission, and to devise effective tactics to alleviate the strain of epidemic prevention and control. By examining those who are vulnerable, the risk of epidemic transmission can be more precisely predicted and reacted to, thus enhancing the prevention and control effect. This paper first defines the definition and scope of susceptible people, and then makes an in-depth analysis of the characteristics of susceptible people, including physiological characteristics, social characteristics and psychological characteristics. On this basis, this paper puts forward targeted prevention and control strategies, including strengthening health monitoring, enhancing public awareness of epidemic prevention, and optimizing the allocation of medical resources. This paper also discusses the feasibility and the implementation difficulties of the prevention and control strategies, and puts forward the corresponding solutions. By delving deeply into the traits of vulnerable populations, more precise strategies and measures can be devised to avert and manage epidemics, thus diminishing the danger of contagion. To guarantee public health security and social equilibrium, it is essential to reduce the strain of epidemic prevention and control.